Podeželje in razvoj gastronomije v Sloveniji: Teritorialne kolektivne blagovne znamke po modelu ’Izvorno slovensko’ v letu 2020 (University of Maribor Press, 2021)
Rural Area and Gastronomy Development in Slovenia: Territorial Collective Brands According to the ‘Authentic From Slovenia’ Model in 2020.The publication presents the scientific background and the importance of establishing territorial collective brands according to the Authentic from Slovenia model for the development of the Slovenian countryside and building gastronomic tourism, which is based on short supply chains from the field to the plate and establishes a system of quality and origin of food and materials for all accompanying stakeholders build a gastronomic rural tourist destination. The model is based on systematic integration, building a rating system and visual image of a collective brand, training, consulting, quality assessment, granting the right to use the certificate, establishing a marketing, sales, logistics and continuous quality assurance system through planned monitoring of product quality and origin. At the first level, we build the primary offer, namely training and advising crop and food product providers to build stories with local added value that can be included in the dishes by caterers. On the second level, we create a locally recognizable offer of accommodation capacities, gastronomic events and experiences. The third level is intended for ambassadors of the collective brand, who combine several of the mentioned activities under one roof, and reception tourist agencies. The fourth level is intended for the construction of a portal that enables communication between stakeholders within the destination and attracts the attention of demanding gastronomy researchers who are willing to devote their time and money to exceptional boutique experiences. All activities are coordinated with the activities of the Slovenian Tourist Board and MERT and an excellent orientation for Slovenia - European Gastronomic Region of Europe 2021.